Effect of Lactobacillus salivarius supernatant against growth and biofilm formation of some pathogenic microorganisms (Baghdad Science Journal, 2016)
The Inhbititory effect of cocentrated and non-cocentrated supernatant of the probiotic Lactobacillus salivarius against growth of some potential pathogenic microorganisms which included Pseudomonas eruginosa, Klebsiella spp, Escherichia coli and Candida albicans. The results were diffusion assay revealed that concentrated and non-concentrated supernatant had inhitory effect against pathogenic bacteria with inhibition zone renged between 13-17mm while inhibition effect of concentrated supernatant against C.albicans was inhibition zone 8mm. On the other hand, the effect of these suprnatant against biofilm formation of the tested microorganisms was studied. The result showed that the concentrated supernatant had inhibitory effect on biofilm formation for all tested microorganisms with percentage (28-29)% against tested bacteria and (23)% against C.albicans.